A randomised controlled trial of short term growth and collagen turnover in asthmatics treated with inhaled formoterol and budesonide. Issue 4 (1st October 2000) - Heuck, Carsten; Heickendorff, Lene; Wolthers, Ole D
Abstract : AIMS: To determine effects on short term growth and collagen turnover of adding formoterol (Eformoterol) to half the glucocorticoid dose in children with asthma, treated with inhaled budesonide (Pulmicort Turbuhaler). DESIGN: A randomised double blind, placebo controlled crossover study with two six-week periods. SETTING: Outpatient clinic in secondary referral centre. SUBJECTS: A total of 27 prepubertal children aged 6–13 years. INTERVENTIONS: Formoterol 12 μg and dry powder budesonide 100 μg twice daily in one period; placebo and dry powder budesonide 200 μg twice daily in the other. OUTCOME MEASURES: Primary outcome measures were lower leg growth rate, and serum and urine markers of type I and type III collagen turnover. Secondary outcome measures were inflammation markers in serum, and parameters of asthma control. RESULTS: During budesonide 200 μg twice daily treatment, mean lower leg growth rate was 0.14 mm/week (p = 0.02) lower than during the formoterol and budesonide period. Similar statistically significant effects on markers of collagen turnover were found, whereas inflammation markers and asthma control did not vary statistically significantly between the two periods. CONCLUSIONS: In children treated with inhaled glucocorticoids, halving the dose and adding formoterol is associated with faster short term growth and an increase in markers of collagen turnover, with no loss of asthma control.